Diffusion of artificial intelligence-based learning innovation: A case study in MTs Muhammadiyah Tawangsari Sukoharjo - Laksana, Novianto Yudha; Rengkaningtias, Ayu Usada; Handayani, Wuri (Universitas Negeri Yogyakarta, 2023)
Madrasah Tsanawiyah Muhammadiyah Tawangsari is a junior high school level educational institution that bases its curriculum on Islamic principles and progressively applies information technology (IT) on the foundation of Muhammadiyah values. This study aims to determine the process of diffusion of innovation in technology-based learning, focusing on the role of teachers as agents of change in applying artificial intelligence in the context of learning. The research method used was qualitative descriptive, involving in-depth interviews with four teachers who had key roles in introducing the innovation. The results showed that most teachers have received information about the use of artificial intelligence through various socialization activities, workshops, and training. The diffusion of learning innovations in MTs Tawangsari involves various communication channels, including interpersonal communication such as lectures, dialogues, and demonstrations of effective practices; communication through mass media, such as the publication of writings on school websites; and communication through social media, such as Youtube, Instagram, and Facebook. In addition, teachers consider that innovation in post-pandemic learning has significant urgency, with success indicators in the form of increased active student participation in the learning process. In addition, teachers also voiced the need for community platforms and continuous training on artificial intelligence-based learning.